Implementation of Strategic Management In An Effort to Implement Islamic Life Guidelines at Yogyakarta Muhammadiyah University - Saputra, Rizka Maulana; Fauzan, Aris (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Islamic-based educational institutions must be able to produce graduates and academics community who have good and commendable morals. the use of strategic management theory is seen as capable of realizing this. UMY uses this theory as an effort to shape the morals of its graduates and all of its academic community so that they become better and uphold Islamic values. This research article aims to reveal the implementation of strategic management used by UMY in shaping the character of the academic community in accordance with Islamic teachings as stated in the PHIWK. This type of research is qualitative with an analytical descriptive approach. The methods used in this research article are data collection, interviews, documentation and participant observation. To analyze used methods: data presentation, data reduction, and description of phenomena. The findings in this research article are: first, the implementation of PHIWK in the academic community has not gone according to the strategic management flow, this is because there are still several activities that have not been carried out. Second, the program evaluation has not been carried out, due to the absence of an Ad Hoc Team who is fully responsible for the process of implementing the PHIWK program, as in the flow in strategic management.